PENGUKURAN TUBUH BERBASIS ANDROID MENGGUNAKAN TENSORFLOW LITE DAN OPENCV UNTUK PAKAIAN WANITA - Karimatun Nisa’; Okkie Puspitorini; Nur Adi Siswandari; Ari Wijayanti; Nesya Alpha Nanda; Arifin; Muhamad Milchan (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The development of technology and informatics that is increasingly advanced makes human work easier and more efficient. But in the field of tailoring, customer clothing measurements must be present and complete all desired measurements offline. Therefore, VIRTA (Virtual Tailor) is here to make it easier for people to use sewing services without having to go to the place. By using the VIRTA application, customers can take body measurements for making tops and bottoms online. In this final project case study, it is focused on body measurements for making adult women’s suits and skirts, by utilizing Image Processing to get body points that utilize a mobile camera so that measurements can be taken using the Euclidean Distance method, then customers will get body size results in cm and recommendations for the right suit and skirt size.